(untitled) (Global Journal of Human-Social Science, 2022)
For the enhancement of distant education and learning through web the practice of e-learning has initiated in late 1990s Because of the significant growth of information and technology the adoption of e-learning became famous globally in late 2000s By the mid of 2010s utilization of electronic devices computers laptops mobile phones and tablets which supports internet connectivity were prominently used by Indian educational institutions to facilitate e-learning process to educate the students through online platforms In the later part of 2010 Indian organizations in collaboration with foreign companies developed their own web-based software and application in order to persuade the practice of e-learning for the students With reference to traditional learning e-learning was adopted in a few numbers Since the outbreak of pandemic issue Covid-19 lockdown and pandemic protocols leads to closure of schools and colleges across the country As a result educating the students through online e-learning served as the full time replacement for traditional learning Although educating students through e-learning made an appropriate replacement for traditional learning students across many parts of India subjected to confront certain issues as well as merits while learning through online On consideration with perception of students the article is aimed at investigating the positive and negative attributes of e-learning among Indian students based on the existing literary works